Cardiovascular and renal outcomes with sodium glucose co-transporter 2 inhibitors in patients with type 2 diabetes mellitus: A system review and network meta-analysis - Tian, Lei; Ai, Sinan; zheng, Huijuan; Yang, Hanwen; Zhou, Mengqi; Tang, Jingyi; Liu, Weijing; Zhao, Wenjing; Wang, Yaoxian (Frontiers in Pharmacology, 2022)
Cardiovascular and renal impairment are the most common complications of type 2 diabetes mellitus (T2DM). As an emerging class of glucose-lowing agents sodium glucose transporter 2 (SGLT2), possesses profitable effects on cardiovascular and renal outcomes in patients with T2DM. The aim of this study is to assess the efficacy of different SGLT2 inhibitors for cardiovascular and renal outcomes for patients with T2DM. We performed a systematic search of PubMed, Embase, and the Cochrane library was performed from inception through November 2021. Randomized clinical trials enrolling participants with T2DM were included, in which SGLT2 inhibitors were compared with each other or placebo. Cardiovascular outcome or renal outcome information was required in these included trials. These outcomes included all-cause mortality, cardiovascular mortality, hospitalization for heart failure, and a renal composite outcome. Ten trials enrolling 68,723 patients were included. Compared with placebo groups, Canagliflozin (HR, 0.85[95%CI, 0.75–0.98]), ertugliflozin (HR, 0.93[95%CI, 0.78–1.11]), and sotagliflozin (HR, 0.94[95%CI, 0.79–1.12]) were associated with a reduction in all-cause mortality. Canagliflozin (HR, 0.84[95%CI, 0.72–0.97]), dapagliflozin (HR, 0.88[95%CI, 0.79–0.99]), empagliflozin (HR, 0.62[95%CI, 0.49–0.78]), ertugliflozin (HR, 0.92[95%CI, 0.77–1.10]), and sotagliflozin (HR, 0.88[95%CI, 0.73–1.06]) were associated with a reduction in cardiovascular mortality; Canagliflozin (HR, 0.64[95%CI, 0.53–0.77]), dapagliflozin (HR, 0.71[95%CI, 0.63–0.81]), empagliflozin (HR, 0.65[95%CI, 0.50–0.85]), ertugliflozin (HR, 0.70[95%CI, 0.54–0.90]), and sotagliflozin (HR, 0.66[95%CI, 0.56–0.77]) were associated with a reduction in hospitalization for heart failure. Dapagliflozin (HR, 0.55[95%CI, 0.47–0.63]), Empagliflozin (HR, 0.54[95%CI, 0.39–0.74]), canagliflozin (HR, 0.64[95%CI, 0.54–0.75]), sotagliflozin (HR, 0.71[95%CI, 0.46–1.09]), and ertugliflozin (HR, 0.81[95%CI, 0.63–1.04]) were associated with a reduction in the renal composite outcome. All SGLT2 inhibitors showed a reduction in cardiovascular mortality, hospitalization for heart failure, renal composite outcomes and all-cause mortality. Canagliflozin and empagliflozin seemed to have the same efficacy in reducing hospitalization for heart failure, but empagliflozin had advantage in reducing cardiovascular mortality, whereas dapagliflozin most likely showed the best renal composite outcomes.